Ethical Disputes over Freebies and Gifts in Journalism Practice: An Analysis of 133 Media Ethics Codes - Yifei Zhao; Jing Niu (Studies in Social Science & Humanities, 2024)
How do media ethics codes regulate journalists’ treatment of freebies in relation to the public’s right to journalism? This study examines 133 media ethics codes from 87 countries and regions. The analysis reveals that most codes overlook the issue of freebies in daily news practice. Among the 133 codes, 49 explicitly address freebies, with varying degrees of specificity, generally categorized into absolute prohibition, relative prohibition, and intermediate attitudes. Ethical codes need more explicit guidance on how journalists should handle freebies to ensure consistency on this issue. Additionally, the normative guidance on freebies requires greater operational feasibility. To enhance the effectiveness of ethical codes in journalism practice, this paper proposes incorporating the principles of bottom line, relevance, and openness in the discussion and revision of ethics codes.